1951
DOI: 10.1139/z51-028
|View full text |Cite
|
Sign up to set email alerts
|

LIFE HISTORY OF LEUCOCYTOZOON SIMONDI MATHIS AND LEGER IN NATURAL AND EXPERIMENTAL INFECTIONS AND BLOOD CHANGES PRODUCED IN THE AVIAN HOST

Abstract: Ducks exposed outdoors in Algonquin Park during the summer became infected with Leucocytozoon simondi and many of them died from the infection in June and July when black flies were abundant. The minimum prepatent period was five and a half days. Young parasites were observed in erythrocytes and lymphocytes; mature gametocytes, as shown by exflagellation of microgametocytes, occurred in round and elongated host cells. Asexual development was observed in the spleen, liver, heart, brain, lung, lymphoid tissue, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1964
1964
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 1 publication
4
36
0
Order By: Relevance
“…Anemia is the most important clinical sign (Maley and Desser 1977) and packed cell volumes may be only 20% of normal (Fallis et al 1951). Other signs are anorexia, lethargy, labored breathing, and diarrhea (Wobeser 1997).…”
Section: Clinical Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anemia is the most important clinical sign (Maley and Desser 1977) and packed cell volumes may be only 20% of normal (Fallis et al 1951). Other signs are anorexia, lethargy, labored breathing, and diarrhea (Wobeser 1997).…”
Section: Clinical Signsmentioning
confidence: 99%
“…Domestic ducks exposed to a single infection and not challenged until 6 weeks later are not resistant to reinfection (Fallis et al 1951). However, ducks exposed to primary infections of L. simondi and then repeatedly exposed to infected vectors over a 3-week period have persistently lower parasitemias than do uninfected control ducks that are exposed to infected vectors at the same time (Fallis et al 1951). Fallis et al (1974) referred to this as a state of premunition.…”
Section: Natural Resistance and Immunitymentioning
confidence: 99%
“…This is probably a reflection of the ecological constraints of Leucocytozoon, which is transmitted by blackflies (Fallis et al 1951). The larvae of these vectors require streams with constant current rates (Zahar 1951), which are common in mountainous areas such as the SNSM.…”
Section: Discussionmentioning
confidence: 99%
“…The positive relationship between WBC levels and the intensity of haemoproteid infection recalls hematological changes that accompany infection with other avian hematozoa, such as Leucocytozoon spp. (Fallis et al 1951, 1956, Desser et al 1968. Even after factoring out the presence/absence or intensity of Haemoproteus infection, species effects on levels of blood leukocytes remained significant (Tables 6 and 7).…”
Section: Island Effectsmentioning
confidence: 97%
“…demonstrated that the sampling program was large enough to discern statistically significant host-parasite combinations. Moreover, blood leukocyte counts, which indicate an individual host's response to its parasite load (Fallis et al 1951, Desser et al 1968, show that both deterministic and historical factors shap e host-parasite associations. Finally, we suggest a framework for gauging the relative importance of these factors based on island biogeographic analysis.…”
Section: Introductionmentioning
confidence: 99%